2003
DOI: 10.1108/02683940310484017
|View full text |Cite
|
Sign up to set email alerts
|

Measuring emotional intelligence: content, construct and criterion‐related validity

Abstract: Many authors claim there is a paucity of evidence for the validity of measures of emotional intelligence (EI). This paper summarises existing information on the reliability and validity of two measures of EI, the Dulewicz and Higgs EIQ and the Bar‐on EQ‐i. It also reports the results of a study on middle managers which investigated the degree to which these two EI instruments measure the same constructs: their concurrent/criterion‐related validity; and the relationship between EI and morale and stress at work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
3
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 14 publications
8
105
3
3
Order By: Relevance
“…Dulewicz et al (2003) stated that the emotional intelligence could be defined based on what relates to our awareness of sensations and emotions and administering it, affecting and influencing the others, persisting and balancing the self-motivation and stimulating it through sense, moral and conscientious behavior (Samadi & Keyvan, 2013). On the other hand, Cherniss and Adlet (2000) stated emotional intelligence as "the ability of controlling the self-emotions, its application in good decision makings and working effectively" (Nwokah & Ahiauzu, 2010).…”
Section: Concept Of Emotional Intelligence (Ei)mentioning
confidence: 99%
“…Dulewicz et al (2003) stated that the emotional intelligence could be defined based on what relates to our awareness of sensations and emotions and administering it, affecting and influencing the others, persisting and balancing the self-motivation and stimulating it through sense, moral and conscientious behavior (Samadi & Keyvan, 2013). On the other hand, Cherniss and Adlet (2000) stated emotional intelligence as "the ability of controlling the self-emotions, its application in good decision makings and working effectively" (Nwokah & Ahiauzu, 2010).…”
Section: Concept Of Emotional Intelligence (Ei)mentioning
confidence: 99%
“…the purpose of this paper is to explore the construct of Ei (including its measurement) from a theoretical viewpoint and to establish the psychometric properties of the SEiS (1998). Dulewicz et al (2003) state that Ei is not a new concept. Mayer, Salovey and Caruso (2004) define the concept of EI as the capacity to reason about emotions, and of emotions to enhance thinking.…”
mentioning
confidence: 99%
“…Highly emotionally intelligent executives are more punctual and take maximum initiatives on the job, they put much amount of efforts to expended their job and have better work performance as compared to their counterparts. The finding is according to (Dulewicz et al, 2003) that found managers' emotional intelligence correlated positively with quality of work life and morale, also (Brackett et al, 2004) concluded that low scores on EI were associated with poor quality peer relations. (Suliman & Al-Shaikh, 2007) revealed that employees with higher levels of EI were found to report higher levels of readiness to create and innovate.…”
Section: Discussionmentioning
confidence: 99%